Particle design and oxidation kinetics of iron-manganese oxide redox materials for thermochemical energy storage. (1st May 2019) - Al-Shankiti, Ibraheam A.; Ehrhart, Brian D.; Ward, Barbara J.; Bayon, Alicia; Wallace, Mark A.; Bader, Roman; Kreider, Peter; Weimer, Alan W.
Highlights: Thermodynamic comparison of doping manganese oxide with Fe2 O3, Al2 O3, & ZrO2 . Redox cycling stability improved with doping manganese oxide with Fe2 O3 . MnFe2O4 spinel, formed from molar 2:1 Fe2 O3 :Mn2 O3 composition is robust. Two reaction mechanisms for oxidation of reduced MnFe2 O4 are identified. Abstract: High-temperature thermochemical energy storage shows promise in aiding concentrating solar power plants to meet variable, grid-scale electricity demand. In this work, manganese oxide-based mixed metal oxide particles have been designed and tested for thermochemical energy storage. Particles are designed for high energy storage capacity, flowability, and physical and chemical stability. We evaluate the effects of Al2 O3, Fe2 O3, and ZrO2 in Mn2 O3 -based spray-dried particles in a TGA between 650 °C and 1200 °C over six consecutive redox cycles. Results are compared with thermodynamic predictions from 400 to 1400 °C under oxidizing and reducing atmospheres. A mixture of 2:1 Fe2 O3 :Mn2 O3 formed iron manganese oxide spinel (MnFe2 O4 ) on calcination, demonstrated the highest thermochemical activity. Intensive mixing was also investigated as a method for preparing MnFe2 O4 spinel. Sodium contained in binders/precursors used for spray drying results in the formation of slag phases which negatively impact spray dried particle redox. Spherical particles formed by intensive mixing provided for superior redox reaction. Differential scanning calorimetry (DSC) was performed on MnFe2 O4 particles prepared by intensive mixing. The oxidation reaction kinetics of MnFe2 O4 was investigated using solid-state kinetics theory and XRD analysis. The reaction proceeds by two different reaction mechanisms. The reaction first proceeds by a diffusion-controlled reaction mechanism (192 ± 2 kJ mol −1 activation energy) with no phase change, followed by a nucleation-growth reaction mechanism (181.4 ± 0.3 kJ mol −1 activation energy). The work reported here supports using low cost MnFe2 O4 spinel, formed by intensive mixing of a 2:1 Fe2 O3 :Mn2 O3 composition, as a desirable thermochemical storage active material. Additionally, these results demonstrate the benefit of operating the redox cycle through a cation-vacancy mechanism where the spinel phase maintains its crystal structure and where the reaction rate is stable/robust regardless of particle size.